New discovery of anti-ulcerative colitis active ingredients of Nostoc commune: p-Hydroxy benzaldehyde. (February 2021) - Xu, Xiaotian; Wei, Chengqiong; Yang, Yingying; Liu, Meng; Luo, Ailin; Song, Hengzhi; Wang, Yuhui; Duan, Xiaoqun
Graphical abstract: Highlights: The alcohol extract of Nostoc commune (AENC) alleviated ulcerative colitis symptoms. p-hydroxy benzaldehyde (HD) was identified as the active ingredient of Nostoc commune responsible for anti-UC activity. p-hydroxy benzaldehyde (HD) ameliorated intestinal mucosal injury. Abstract: Nostoc commune, a natural cyanobacterium, has long been appreciated as a healthy food and was identified for the treatment of ulcerative colitis (UC) . In the present study, p-hydroxy benzaldehyde (HD), a purified compound isolated from the alcohol extract of Nostoc commune (AENC), alleviated dextran sodium sulfate (DSS)-induced colitis, as evidenced by improved weight loss, decreased disease activity index (DAI) scores, reduced colon shortening, reduced myeloperoxidase (MPO) activity and attenuated pathological injuries of colonic tissues through downregulating the protein and mRNA expression of tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6). Moreover, HD has demonstrated in vitro efficacy against UC. Notably, HD significantly upregulated the mRNA expression of E-cadherin in DSS-induced colitis mice and HT-29 cells stimulated with lipopolysaccharide (LPS). Overall, we offer a fresh perspective on the main anti-UC ingredients in Nostoc commune . HD is a new active ingredient of Nostoc commune that alleviates DSS-induced colitis and exerts an anti-colitis effect by ameliorating intestinal mucosal injury by downregulating the expression of proinflammatory cytokines.